Analysis of Domain Addressed and Subdivisions of Anatomy Emphasized in Spotting Stations in Anatomy Part of First Professional MBBS Examination (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Assessment of any educational program should implement purpose of the learning objectives. Learning objectives are prepared with the help of several models such as SOLO (Structure of observed learning Outcomes) taxonomy, Bloom’s Taxonomy etc. The most commonly used classification system is “Bloom’s taxonomy to develop learning objectives” which describes the domains of educational objectives and divides the domains into three categories a) cognitive domain b) psychomotor domain c) affective domain.Objectives: To observe the domains of the questions of soft part-portion of Spotting stations to fulfill the learning objectives set by the curriculum in Anatomy professional examination in the background of Bloom’s Taxonomy. The research also tries to find out the subdivisions of Anatomy preferred more and regions of Gross Anatomy more emphasized in soft part-portion of Spotting stations.Methods: This cross sectional study held in the Department of Anatomy in Armed Forces Medical College (AFMC) from August 2015 to December 2018. Data (questions of soft part-portion of Spotting stations and ‘answer key’s) are collected from seven different medical colleges affiliated under Dhaka University. A total fifty-two day’s questions with ‘answer key’s are taken for the study from the first professional examination held on May 2013 and May 2014. For the purpose of the study each question is divided into ‘Item’, ‘Part’s and ‘Segment’s. Moreover verbs of the segments are then analyzed in the form of ‘statement’, ‘list’ and ‘single name’ and Anatomy is subdivided into Gross Anatomy, Histology and Developmental Anatomy.Result: A total 774 items, 1571 parts, 2048 segments are analyzed. The verbs used to address the levels of cognitive domain in the questions reveals that ‘identification’ is mostly (76.62%) used in supplied figure followed by radiology (52.05%) model (41.89%) viscera (38.82%) and dissection (24.95%) stations. ‘Statement’ mostly used as verb by dissection (37.28%) and minimum in supplied figure (11.6%) stations. Similarly ‘list’ is mostly used in viscera (23.14%) and ‘single name’ is mostly used verb in dissection stations. Maximum (89.2%, 92.47%, 90.54% and 81.82%) questions are asked from Gross Anatomy subdivision in viscera, radiology, model and in supplied figure stations respectively. In case of viscera stations about one third (34.62%) and one fourth (25.62%) questions are from the thorax and abdomen proper respectively and around 15% questions cover pelvis, (10.54%) head neck, (12.34%) and brain (16.88%) respectively. Nearly half (46%) of the figure station use supplied figures as a ‘tool’. Maximum (39%) figures are used from brain where supplied figures are used as a ‘tool’ and no figure used from lower limb.  When instructed to ‘draw and label’, 50% are from region of brain and less than 20% from other regions.             Conclusion: From the findings it can be easily perceived that though Spotting examination is part of practical examination but in our country but it mainly involves in assessing factual knowledge of Anatomy which can hardly meet the demand of the objectives set by the curriculum.JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 59-65